Introducing a professional capabilities framework for social work in Aotearoa New Zealand - Ballantyne N; Beddoe L; Hay K; Maidment J; Walker S; Merriman C (Aotearoa New Zealand Association of Social Workers, 2022)
INTRODUCTION: This article discusses the findings from a project on enhancing the professional capabilities of newly qualified social workers. Existing capability and competence frameworks are reviewed, and components of a draft Aotearoa New Zealand Professional Capabilities Framework (ACPF) are outlined. METHODS: This phase of the research programme began with a literature scan of five social work professional capability frameworks then used this information, data from earlier parts of the study, and a series of co-production workshops with key stakeholders to draft a professional capabilities framework for newly qualified and more experienced social workers. FINDINGS: Analysis of the existing frameworks and data from the co-production workshops identified seven core values and 10 core capabilities to guide early-career and more experienced social work practitioners in Aotearoa New Zealand. IMPLICATIONS: Professional capabilities frameworks can guide and inform the practice and learning of all social workers. Following further stakeholder engagement, especially with tangata whenua (Indigenous people of Aotearoa New Zealand), it is strongly recommended that the Social Workers Registration Board considers the adoption or adaptation of the APCF as an alternative to the current competence standards.